Business Feasibility Analysis in Agribusiness: Case Study on Sustainable Agriculture Sector - Rizal Perlambang CNAWP (Maneggio, 2025)
This study aims to analyze the business feasibility in the sustainable agriculture sector through a case study of organic farming enterprises in Indonesia. This research employs a descriptive qualitative approach with a case study method to explore in depth the market, technical, financial, environmental, and social aspects of sustainable agricultural practices. Data were collected through in-depth interviews, direct observation, and documentation, which were then analyzed using business feasibility analysis. The results of the study show an increasing demand for environmentally friendly organic products, both in local and international markets, although challenges remain in production capacity and access to financing. Technically, the use of eco-friendly technologies and sustainable farming practices can reduce negative environmental impacts. From a social perspective, this business contributes to improving farmers' welfare and empowering local communities. Nevertheless, business development requires support from various stakeholders to overcome existing obstacles and scale up the enterprise.